Rapid Analysis of Acrylamide in Tap and Well Water Samples by Solvent Terminated Dispersive Liquid–Liquid Microextraction Followed by GC–FID - Sayah, Maryam; Kiarostami, Vahid (Bulletin of environmental contamination and toxicology, 2019)
A fast, green and low cost method for analysis of acrylamide in tap and well water has been presented for the first time using solvent terminated-dispersive liquid liquid microextraction (ST-DLLME) with a simple equipment which does not need centrifugation step followed by GC–FID. The use of one variable at a time optimization method revealed that methanol and octanone were the superior disperser and extraction solvents, respectively. A central composite design (CCD) as a response surface methodology was used for multivariate optimization of five independent factors (volumes of extraction and dispersive solvents, pH, salt addition and extraction time) on the extraction efficiency. Under CCD optimal conditions, the linear range, detection limit (S/N = 3) and quantitation limit (S/N = 10) were 0.1, 0.3 and 0.3–550 ng mL −1 , respectively. In these circumstances, the recoveries for real samples (tap and well water) spiked with 0.5, 1 and 10 ng g −1 were in the acceptable range (90.8%–94.1%). In comparison with other methods in the literature, the suggested ST-DLLME approach showed the best analytical performance. The presented green method has potential application as a routine method in the environmental and analytical laboratories for analysis of acrylamide in water samples.